Maxillary Swing Approach for Removal of Palatal Carcinoma: A Modified Procedure - Tsutomu Nomura; Megumi Kishimoto; Hirohisa Iwaki; Atsushi Ochi; Seiji Kishimoto (Case Reports in Otolaryngology)
Introduction. We report a modification of the maxillary swing approach to remove a palatal tumor while preserving the anterior alveolar area. Methods. Case report using clinical records. Results. The patient was a 54-year-old male. TNM grade was T4bN0M0, and invasion to the base of the pterygoid process was seen. Two courses of induction chemotherapy were administered prior to the operation. Because there was no evidence of anterior maxillary invasion, the maxillary swing approach was chosen. The left anterior maxilla was cut and swung laterally, preserving the blood supply. After removal of the palatal tumor, the maxilla was repositioned and the defect was restored with an anterior lateral thigh flap. Postoperative course was typical, and facial appearance, speech, and masticatory function were satisfactory. Conclusions. This technique is particularly useful for preserving appearance as well as speech and mastication.